"Mit trauervollem Blick": The Time of Seeing and Lyric Subjectivity in Rainer Maria Rilke's "Orpheus. Eurydike. Hermes" and "Pietà". (October 2015) - Sorenson, Alexander
Abstract : In this paper, I analyze two poems from Rainer Maria Rilke's Neue Gedichte in which the act of seeing attains a poetic status, namely "Orpheus. Eurydike. Hermes" and "Pietà." This ocular poeticity derives not merely from the visual features of the beheld objects, but more fundamentally from the temporal implications of seeing. In the crucial scene of "Orpheus. Eurydike. Hermes, " an instance of third‐person observation is recounted as narrative retrospection, while in "Pietà, " a first‐person observation is narrated in the moment as a subjective concatenation of temporal categories. These valences of the gaze are further traced in two artworks which are thought to have inspired the poems: a Roman bas‐relief depicting Orpheus, Hermes, and Eurydice, and Auguste Rodin's Le Christ et la Madeleine . In the poems and their statuary antecedents, it is not what is seen but rather the temporal substrate of seeing that indexes the gaze as variedly poetic, and consequently as intrinsic to subjectivity.